Sejarah Munculnya Aliran Al-Maturidiyah dan Pokok-Pokok Ajarannya - Arfah, Andi Muhammad Awaluddin; Jafar, Usman; Santalia, Indo (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The Asy'ariyah and Al-Maturidi groups emerged because of the dissatisfaction of Abul Hasan Al-Asy'ari and Abu Manshur Muhammad ibn Muhammad ibn Mahmud Al-Maturidi with the arguments and opinions expressed by the Muktazilah group. In its journey, Asy'ari itself experienced three periods in understanding its creed, namely Muktazilah, contra Muktazilah, and Salaf. Between Asy'ariyah and Maturidiyah themselves there are several differences, including in the following matters: About the nature of God, about deeds humans, about the Koran, God's obligations, the perpetrator of major sins, God's form, and also God's promises. The main points of Al-Maturidiyah's teachings basically have many similarities with the al-Ash'ariyah school of reforming Mu'tazilah opinions. The differences that arise can be said to be only in the explanation of their teachings or in branch issues. If al-Maturidi's thoughts are studied more closely, it will be found that al-Maturidi gives greater authority to human reason compared to Ash'ari. However, among the Maturidiah themselves there are two groups that also have different tendencies of thought, namely the group Samarkand, namely the followers of al-Maturidi himself whose theological understandings are closer to the Mu'tazilah understanding and the Bukhara group, namely the followers of al-Bazdawi who tend to be Ash'ariyah.